Evaluasi Program ASELA DIJAKETI (Ayo sekolah lagi Pendidikan kejar paket dan inklusi) dalam menurunkan angka putus sekolah di Kota Tegal - Intan Nur Briliana; Yuwanto Yuwanto (Journal of Politic and Government Studies, 2026)
The high number of Out-of-School Children (OSC) and school dropouts in Tegal City indicates that the implementation of the 12-Year Compulsory Education Program has not been optimal. This condition is influenced by limited family economic capacity, low learning motivation, and restricted access to formal education. In response, the Tegal City Government, through the Department of Education and Culture, implemented the ASELA DIJAKETI Program (Ayo Sekolah Lagi Pendidikan Kejar Paket dan Inklusi) to expand educational access through equivalency and inclusive education services. This study aims to evaluate the implementation of the ASELA DIJAKETI Program by focusing on the implementation process, program outcomes, and implementation constraints. The study employs a descriptive qualitative method. Data were collected through in-depth interviews, documentation, and literature review involving the Tegal City Department of Education and Culture, administrators of the Learning Activity Center (SKB), program participants, and alumni. Data analysis was conducted using the policy evaluation framework developed by Bali, Capano, and Ramesh, which includes political, analytical, and operational dimensions. The findings indicate that the ASELA DIJAKETI Program has positively contributed to restoring access to education for out-of-school children and school dropouts through equivalency education Programs A, B, and C. However, the program has not yet achieved optimal effectiveness due to limited capacity of educational facilitators, participants’ socioeconomic conditions, and low learning motivation among some participants. Therefore, strengthening inter-agency coordination, enhancing human resource capacity, and ensuring sustained policy support are necessary to improve the program’s effectiveness.